Bringing Covid to College: Incoming First-Year College Students' Making Meaning of the Pandemic. Issue 3 (June 2023) - Velez, Gabriel; Hoekstra, Erin; Nemanich, Samuel; Jessup-Anger, Jody; Herteen, Max
As time passes from the start of the COVID-19 pandemic in 2020, new cohorts of emerging adults transition to college, carrying with them experiences and effects of the pandemic on their lives and development. This study uses semi-structured interviews and reflexive thematic analysis to investigate how a cohort of 36 young people made narrative meaning of the pandemic in relation to their identities. Data were collected at the beginning of their first year at college and focused on their experiences of the pandemic, its impact on their lives, and the lessons they took away from it. Findings demonstrate that even amid deep and varied challenges, young people coped in nuanced ways and some built narratives of personal growth, development, new social identities, and maturing values. The study contributes to greater depth in understanding the impacts of the pandemic on young people as they develop into emerging adults.